Caffeine for the Pharmacological Treatment of Apnea of Prematurity in the NICU: Dose Selection Conundrum, Therapeutic Drug Monitoring and Genetic Factors - Long, Jia-Yi; Guo, Hong-Li; He, Xin; Hu, Ya-Hui; Xia, Ying; Cheng, Rui; Ding, Xuan-Sheng; Chen, Feng; Xu, Jing (Frontiers in Pharmacology, 2021)
Caffeine citrate is the drug of choice for the pharmacological treatment of apnea of prematurity. Factors such as maturity and genetic variation contribute to the interindividual variability in the clinical response to caffeine therapy in preterm infants, making the optimal dose administered controversial. Moreover, the necessity for therapeutic drug monitoring (TDM) of caffeine is still worth discussing due to the need to achieve the desired target concentrations as well as concerns about the safety of higher doses. Therefore, we reviewed the pharmacokinetic profile of caffeine in preterm infants, evidence of the safety and efficacy of different doses of caffeine, therapeutic concentration ranges of caffeine and impact of genetic variability on caffeine therapy. Whereas the safety and efficacy of standard-dose caffeine have been demonstrated, evidence for the safety of higher administered doses is insufficient. Thus, preterm infants who lack clinical response to standard-dose caffeine therapy are of interest for TDM when dose optimization is performed. Polymorphisms in pharmacodynamics-related genes, but not in pharmacokinetics-related genes, have a significant impact on the interindividual variability in clinical response to caffeine therapy. For preterm infants lacking clinical response, how to develop individualized medication regimens for caffeine remains to be explored.